The effectiveness of non-invasive brain stimulation in enhancing lower extremity function in children with spastic cerebral palsy: Protocol for a systematic review and meta-analysis - Clàudia Arumí-Trujillo; Francisco José Verdejo-Amengual; Oriol Martínez-Navarro; Jord J.T. Vink; Fran Valenzuela-Pascual (MethodsX)
Non-invasive brain stimulation (NIBS11 Non-invasive brain stimulation.) techniques have emerged as a promising non-pharmacological adjunct to neurorehabilitation. Children with Cerebral Palsy (CP22 Cerebral Palsy.) exhibit altered cortical excitability, and while CP remains incurable, physiotherapy combined with other interventions is essential for managing motor dysfunction. Although some studies have examined NIBS using various stimulation parameters, there is limited evidence regarding its effects on the lower extremities and optimal administration protocols. This review aims to evaluate the effectiveness of NIBS techniques, such as transcranial direct current stimulation (tDCS33 Transcranial Direct Current Stimulation.) and repetitive transcranial magnetic stimulation (rTMS44 Repetitive Transcranial Magnetic Stimulation.), for the treatment of motor function in spastic cerebral palsy, specifically in the lower extremity. A systematic search will be conducted in databases including MEDLINE, CINAHL Plus, EMBASE, Scopus, ISI Web of Science, and the Cochrane Central Register of Controlled Trials. The search strategy will follow the PICO framework (Participants, Intervention, Comparison, Outcomes), focusing on randomized controlled trials (RCTs). Two independent reviewers will manage screening, selection, data extraction, risk of bias assessment, and grading of evidence. This review will provide key insights into the effectiveness of NIBS for lower-extremity function in children with spastic CP, guiding future research and clinical applications.